UNIVERSITY AS A VALUABLE UNIT OF SELF- KNOWLEDGE - Elena A. Veliyeva (World Science, 2020)
This article discusses the trend of successful university activity as an integral unit of the educational system with its proper management. Successful activities of the university are realized in the formation and maintenance of the internal atmosphere of the university itself. A manifestation of such activity is the open character of university management (transparency in making important decisions, the elective nature of governing bodies and staff appointments), as well as the tendency to provide a centralized information environment for staff (creating an extensive internal electronic information network covering all structures). This activity is essential for maintaining the cohesion of labor collectives in higher education. Elements of competitive relations are among the university staff in the field of higher education. The purpose of competition is to attract quantitative and qualitative applicants, as well as gaining public recognition. Most teachers are proud of the prestige of the university. This article analyzes socially significant and personal values. The student’s personal and professional growth is a qualitative change in his position and role in society. The source of personal and professional development are the contradictions between the achieved level of student development and the requirements that the university community makes to him. Self-educational activity is the main condition necessary for the development of professional competence among students of engineering universities at the present stage. Given the variety of definitions of self-education, we can highlight some of its essential features, such as: an independent search for additional information, the acquisition of knowledge and on-going development. Further, the article expresses the opinion that self-education can exist only on the basis of deep perspective internal motives. Individual cases of searching for answers to questions of interest to a person under the influence of any motives cannot be considered self-education. In this paper, self-education is considered as purposeful, systematic, cognitive activity managed by students themselves, necessary for improving education.